2015
DOI: 10.1016/j.jare.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different night-time temperatures and cultivation durations on the polyphenolic contents of lettuce: Application of principal component analysis

Abstract: The present study was conducted to characterize the polyphenolic contents of lettuce leaves grown under different night-time temperatures (4, 12, and 20 °C) and cultivation durations (5, 15, and 20 days) using high performance liquid chromatography-tandem mass spectrometry (LC/MS/MS). The assay method was validated based on specificity, linearity, accuracy, precision, and the performance limit. The total polyphenolic contents were highest (2462.6 mg/kg) after transplantation at a night temperature of 20 °C on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
4
22
1
1
Order By: Relevance
“…A caffeoyltartaric acid (peak 10 : Rt = 9.06 min, λmax = 301, 323 nm) was detected in the extracted MS chromatogram set at m/z 311 in the negative ion mode, presenting the corresponding fragmentation pattern: The dehydrated protonated molecule at m/z 293 was the base peak in low energy function; and intense fragments of the deprotonated tartaric ( m/z 149) and caffeic ( m/z 179) acids and the losses of water ( m/z 293) and CO 2 ( m/z 135; base peak) were observed in the high energy function. Two isomers of caffeoyltartaric acid have been already reported in lettuce in literature, also in green and red oak‐leaf cultivars …”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…A caffeoyltartaric acid (peak 10 : Rt = 9.06 min, λmax = 301, 323 nm) was detected in the extracted MS chromatogram set at m/z 311 in the negative ion mode, presenting the corresponding fragmentation pattern: The dehydrated protonated molecule at m/z 293 was the base peak in low energy function; and intense fragments of the deprotonated tartaric ( m/z 149) and caffeic ( m/z 179) acids and the losses of water ( m/z 293) and CO 2 ( m/z 135; base peak) were observed in the high energy function. Two isomers of caffeoyltartaric acid have been already reported in lettuce in literature, also in green and red oak‐leaf cultivars …”
Section: Resultsmentioning
confidence: 70%
“…Taking into account all the above considerations, the chromatographic peaks were tentatively identified as follows: 1 , trans ‐3‐CQA; 2 , trans ‐1‐CQA; 3 , trans ‐5‐CQA; 4 , cis ‐3‐CQA; 5 , trans ‐4‐CQA; 6 , cis ‐5‐CQA; and 7 , cis ‐4‐CQA. Only 3 CQA isomers had been reported previously in green lettuce, ie, 5‐CQA, 3‐CQA, and an unidentified CQA isomer, and only 5‐CQA in the red oak‐leaf cultivar trans ‐5‐CQA ( 3 ) was the major phenolic compound in both oak‐leaf cultivars, as occurs in other lettuce varieties . The following major CQAs were cis ‐5‐CQA and trans ‐3‐CQA (40% and 5% of the total intensity of trans ‐5‐CQA, respectively in the green cultivar, and about 5% for each CQA isomer in the red cultivar).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Dong et al studied soluble flavonoids and found that “Xiangfen 1” banana can be a rich source of natural antioxidants in human diets. Jeong et al (2015) characterized the polyphenolic contents of lettuce leaves grown under different night-time temperatures and cultivation. Plant-derived phenylpropanoids (PPPs) compose the largest group of secondary metabolites produced by higher plants (Korkina et al, 2011).…”
mentioning
confidence: 99%